1998
DOI: 10.1038/sj.sc.3100530
|View full text |Cite
|
Sign up to set email alerts
|

Camel collision as a major cause of low cervical spinal cord injury

Abstract: One hundred and forty patients with low cervical spinal cord injuries, who were admitted to the Riyadh Armed Forces Hospital over the past 10 years were reviewed. Motor vehicle accidents constituted 119 (85%) of the patients. Camel collisions were a major cause of vehicle accidents 39 (33%), after rollover accidents 70 (59%), and much more than head on collisions 9 (7.5%). Male to female ratio was 14 : 1 with a mean age of 32 years. Camel collision although a commonly observed cause of motor vehicle accidents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…12,13 As camels are huge in Saudi Arabia so its collision with vehicle are available. 14,15 Synthetic predator scent is another effective method for saving wildlife. 16…”
Section: Discussionmentioning
confidence: 99%
“…12,13 As camels are huge in Saudi Arabia so its collision with vehicle are available. 14,15 Synthetic predator scent is another effective method for saving wildlife. 16…”
Section: Discussionmentioning
confidence: 99%
“…According to another research, the yearly occurrence of CVCs in Saudi Arabia is over 600, with a mortality rate of one out of every four CVCs, a rate that is six times higher than all other forms of road traffic incidents. A study conducted at Riyadh Armed Forces Hospital in Saudi Arabia (1998) reported that most patients with low cervical spine injuries were due to motor vehicle accidents, and camel collisions were shown to be a primary contributor to traffic accidents [39] . Camel accidents are prevalent in the evenings, when camels that stay in the desert, generally unattended, roam around in herds of four to six, often unexpectedly crossing roadways [39] .…”
Section: Epidemiology Mechanisms and Patterns Of Camel And Vehicle Re...mentioning
confidence: 99%
“…A study conducted at Riyadh Armed Forces Hospital in Saudi Arabia (1998) reported that most patients with low cervical spine injuries were due to motor vehicle accidents, and camel collisions were shown to be a primary contributor to traffic accidents [39] . Camel accidents are prevalent in the evenings, when camels that stay in the desert, generally unattended, roam around in herds of four to six, often unexpectedly crossing roadways [39] . There are no specified camel crossing routes, and camel owners frequently break the fence constructed in various locations to allow the camels to cross.…”
Section: Epidemiology Mechanisms and Patterns Of Camel And Vehicle Re...mentioning
confidence: 99%
“…Accidents involving animals are reported worldwide. Animal involved in these accidents varies in different countries 1,2,3,4,5 . It includes camels, kangaroo, deer etc.…”
Section: Introductionmentioning
confidence: 99%
“…It includes camels, kangaroo, deer etc. 1,2,3,4,5 . Data from these studies has helped in reducing such accidents by various remedial measures in respective countries 5,6,7 .…”
Section: Introductionmentioning
confidence: 99%